Optimization of Culture Media Ingredient and Inoculum On the Yield of Tubifex Worms at Pilot Scale Level - Haque, Md Inja mamun; Hasan, Mahmud (Dhaka University Journal of Biological Sciences, 2022)
While the first experiment evaluated the effect of media ingredient mustardoil cake wetted in cattle blood, rice gruel and subsurface clean water, the secondexperiment focused on the effects of two doses of media levels 75 and 100 mgcm-2 and two levels of inoculums 75 and 100 mg cm-2, on the yield of tubifexworms. Wet medium did not have significant effect on the yield of tubifexworms harvested after 70-day culture duration. Applying 75 mg cm-2 mustard oilcake as media ingredient resulted in the significantly higher (p < 0.05) yield thanthat of 100 mg cm-2. On the contrary, worms’ inoculum at the rate of 100 mg cm-2 gave significantly higher yield than did the 75 mg cm-2 inoculum. The results ofthis study have demonstrated that mustard oil can be used as the only culturemedia ingredient and the combination of 75 mg cm-2 media ingredient and 100mg cm-2 worm’s inoculum is the best combination at pilot scale level culture oftubifex. Dhaka Univ. J. Biol. Sci. 31(1): 193-201, 2022 (January)